Item selection and validation of a brief, 20-item version of the Differentiation of Self Inventory—Revised. (July 2016) - Sloan, David; van Dierendonck, Dirk
Abstract: The 46-item Differentiation of Self Inventory—Revised (DSI-R) (Skowron & Schmitt, 2003) is perhaps the most widely used and psychometrically validated instrument measuring the family systems theory (Bowen, 1978) concept of differentiation of self. Given the substantial length of the DSI-R, Drake et al. (2015) offered the Differentiation of Self Inventory—Short Form (DSI-SF). However, based on limitations of the DSI-SF, we empirically validated a brief version of the 4-factor DSI-R using data from two adult samples (Sample 1: n = 541; Sample 2: n = 203). First, we conducted an EFA on the full 46-item DSI-R scale on Sample 1 to help us identify items most strongly representing each factor. Then we conducted CFAs comparing the model fit between our brief DSI, the DSI-SF, and the full DSI-R on both samples. Results indicated that the brief DSI had the strongest model fit in both samples. Finally, a comparison of associations among the brief DSI, the DSI-SF, and full DSI-R and various relevant variables showed similar correlations. The brief DSI provides counselors and researchers in the areas of psychology, organizational behavior, and business a useful measure of differentiation of self when circumstances prohibit the use of the full DSI-R. Highlights: A brief version of the Differentiation of Self Inventory—Revised is proposed. Study critiques the alternative, the Differentiation of Self Inventory—Short Form. Data from two independent samples showed the brief DSI had the best model fit. Correlations between relevant variables and the three instruments were similar.